A case report of Hodgkin lymphoma in a patient treated with ustekinumab for psoriasis. Issue 21 (22nd May 2020) - Charakopoulos, Emmanouil; Spyrou, Ioannis; Viniou, Nora-Athina; Giannakopoulou, Nefeli; Hatzidavid, Sevastianos; Diamantopoulos, Panagiotis Theodorou
Abstract: Rationale: Ustekinumab is a biological agent that inhibits interleukin 12 and 23 and has been approved for the treatment of moderate and severe plaque psoriasis. There have been case reports that raise concerns about its oncogenic potential. We are the first authors to report a case of Hodgkin lymphoma in a psoriatic patient receiving ustekinumab. Patient concerns: A 22-year-old asymptomatic female patient presented to our department to investigate an enlarged cervical lymph node. Her past history was unremarkable, except for psoriasis since age 13. Two months before presentation the decision to administer Ustekinumab was taken and the patient had already received 3 doses. Diagnoses: During workup a Stage IV Hodgkin lymphoma was discovered. Interventions: Ustekinumab administration was discontinued. The patient received treatment with the ABVD regimen. Outcomes: The patient's disease was refractory to the above-mentioned treatment. Therefore, a more aggressive regimen (BEACOPP escalated) was administered. Lessons: Growing postmarketing surveillance data and case reports indicate that further research is warranted in order to elucidate a potential association between Ustekinumab and malignancy.